Genome collection of Shewanella spp. isolated from spoiled lamb - Palevich, Nikola; Palevich, Faith P.; Gardner, Amanda; Brightwell, Gale; Mills, John (Frontiers in Microbiology, 2022)
The diversity of the genus Shewanella and their roles across a variety of ecological niches is largely unknown highlighting the phylogenetic diversity of these bacteria. From a food safety perspective, Shewanella species have been recognized as causative spoilage agents of vacuum-packed meat products. However, the genetic basis and metabolic pathways for the spoilage mechanism are yet to be explored due to the unavailability of relevant Shewanella strains and genomic resources. In this study, whole-genome sequencing of 32 Shewanella strains isolated from vacuum-packaged refrigerated spoiled lamb was performed to examine their roles in meat spoilage. Phylogenomic reconstruction revealed their genomic diversity with 28 Shewanella spp. strains belonging to the same putative novel species, two Shewanella glacialipiscicola strains (SM77 and SM91), Shewanella xiamenensis NZRM825, and Shewanella putrefaciens DSM 50426 (ATCC 8072) isolated from butter. Genome-wide clustering of orthologous gene families revealed functional groupings within the major Shewanella cluster but also considerable plasticity across the different species. Pan-genome analysis revealed conserved occurrence of spoilage genes associated with sulfur and putrescine metabolism, while the complete set of trimethylamine metabolism genes was observed in only Shewanella sp. SM74, S. glacialipiscicola SM77 and SM91 strains. Through comparative genomics, some variations were also identified pertaining to genes associated with adaptation to environmental cues such as temperature, osmotic, salt, oxidative, antimicrobial peptide, and drug resistance stresses. Here we provide a reference collection of draft Shewanella genomes for subsequent species descriptions and future investigations into the molecular spoilage mechanisms for further applications in the meat industry.